The relationship between dietary compliance and blood sugar levels in diabetes mellitus patient’s - Nanda, Ginanjar Mukti; Rosyid, Fahrun Nur (Jurnal EduHealth, 2024)
People with diabetes who follow a nutritious eating pattern often struggle to adhere to the prescribed diet therapy for lowering blood sugar levels. Adherence to a diverse menu of foods has an effective impact on blood sugar control. This study aims to investigate the relationship between adherence to dietary patterns and blood sugar levels. The research involves participants with diabetes, both those undergoing treatment and those not yet treated. The method utilizes statistical analysis, specifically the Chi-Square Test, with a population of 309 patients and 175 respondents. The results indicate that 121 respondents (69.1%) fall into the compliant category, while 54 respondents (30.9%) do not comply. The research conclusion reveals a p-value of <0.000, indicating that dietary adherence significantly influences blood sugar control.